ADUBAÇÃO FOSFATADA PARA A SUCESSÃO AVEIA PRETA–SOJA A PARTIR DO ESTABELECIMENTO DO SISTEMA PLANTIO DIRETO - Scharr, Danilo Augusto (2015)
In Brazil there are large degraded grazing areas that could be used for grain production. Soil acidity and phosphorus (P) deficiency in these areas are the factors that most limit crop production. The most adequate supply of P can be achieved by proper management of phosphate fertilization and by the choice of the most appropriate fertilizer for each soil type and management. In order to assess the efficiency of the application of phosphate sources with different solubility, with and without anticipation, for a cropping sequence of black oat and soybean in the conversion of degraded pasture to a no-till system, an experiment was carried out on an Oxisol (Typic Hapludox) with high acidity and low P content in the period from 2009 to 2013, in Ponta Grossa, PR, Brazil. Before the establishment of the experiment, soil acidity was corrected through the application of dolomitic lime with incorporation to raise the base saturation in the topsoil (0-20 cm) to 70%. A randomized complete block design was used, with three replications. Seven treatments of phosphorus fertilization with or without anticipation of the soybean fertilization for black oat crop through the application of magnesium thermophosphate (MT), natural reactive phosphate (RF) and fully acidulated phosphate - triple superphosphate (TS) were tested: no P, MT in the oat seed furrow, RF in the oat seed furrow, TS in the oat seed furrow, MT in the soybean seed furrow, RF in the soybean seed furrow and TS in the soybean seed furrow. A cropping sequence of black oat and soybean was conducted four cycles. The annual rate used in the phosphate fertilization treatments was 100 kg ha-1 of P2O5, based on the total P2O5 content of fertilizers. Application of TS in the oat seed furrow provided higher dry matter production and increased nutrient uptake by black oat, in the four years of cultivation, due to increased availability of soil P. Phosphorus fertilization, with or without anticipation, increased P and Mn contents, and reduced concentrations of S and Zn in soybean leaves, especially with the TS use. There was also a reduction in S content and an increase in Mg content in soybean grains with the phosphate fertilization, regardless of source used. The highest soybean yields were obtained with the TS application in the soybean seed furrow in the first crop; in the seed furrow of oat or soybean in the second and third crops; and in the oat seed furrow in the fourth crop. At the end of four cycles of a cropping sequence of black oat and soybean, use of TS with or without anticipation provided greater agronomic efficiency and higher economic returns than sources less soluble in water (RF and MT). The results suggest that in the conversion of degraded grassland to a no-till system with a cropping sequence of black oat and soybean, the phosphorus fertilization of soybean should be done with the fully acidulated source (TS), and the application of this source could be anticipated for the black oat seed furrow.